Proceedings of the 4th International Conference on Sport Science, Health, and Physical Education (ICSSHPE 2019) 2020
DOI: 10.2991/ahsr.k.200214.092
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Speed and Acceleration on 60-Meters Running Test Between Women Soccer and Futsal Players

Abstract: Athlete Speed and acceleration data needed for customizing the athlete training program design. This study is conducted to identify and compare the speed and acceleration of ability between woman Soccer and futsal athlete. The samples used in this study are women soccer and futsal players from Soccer and futsal club, age ranging from 16-17 years old. The athlete performs 60 meters running test, every 10 meters will be recorded the time. Results, Average time 60m running test of women soccer 11.16s and women fu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
2
0
1
Order By: Relevance
“…In women, it shows that height is more effective in the second stage of acceleration. In a study, they reported that female futsal players have higher speed and acceleration than football players (Herman, et al, 2020), which makes us think that leg length and stride length are positive indicators.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In women, it shows that height is more effective in the second stage of acceleration. In a study, they reported that female futsal players have higher speed and acceleration than football players (Herman, et al, 2020), which makes us think that leg length and stride length are positive indicators.…”
Section: Discussionmentioning
confidence: 98%
“…A very good ascent and acceleration technique is required in order for the acceleration ability to develop in accordance with the purpose. Speed and acceleration data are needed to customize the design of the training program for athletes (Herman et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…A modalidade futsal, vem ganhando adeptos de todas as idades em todos os continentes, aumentando sua popularidade, e visibilidade (Fin, 2020). Com menor número de jogadores, dimensões da área de jogo e tempo total da partida, quando comparada ao futebol de campo (Gorostiaga et al, 2009), além das diferenças em relação a superfície em que é praticado (piso rígido) bola e calçado (Ré, 2008;Juntara & Rachman,2019), tem impulsionado a ciência do esporte, para contribuir de forma significativa, avaliando suas características, requisitos físicos, motores e fisiológicos, perfis dos participantes, melhorando e desenvolvendo de forma mais eficiente métodos de treinamento, que visam alcançar um melhor desempenho e resultados (Herman et al, 2019).…”
Section: Introductionunclassified